Nerve Repair by Means of Tubulization: Past, Present, Future - Konofaos, P.; Ver Halen, J. P. (Journal of Reconstructive Microsurgery, 2013)
Peripheral nerve injury may result in injury without gaps or injury with gaps between nerve stumps. In the presence of a nerve defect, the placement of an autologous nerve graft is the current gold standard for nerve restoration. The clinical employment of tubes as an alternative to autogenous nerve grafts is mainly justified by the limited availability of donor tissue for nerve autografts and their related morbidity. The purpose of this review is to present an overview of the literature on the applications of nerve conduits in peripheral nerve repair. Moreover, the different steps that are involved in the design of an ideal nerve conduit for peripheral nerve repair, including the choice of biomaterial, fabrication technique, and the various potential modifications to the common hollow nerve tube, are also discussed.
Keywords: nerve gap; nerve repair; nerve guides; neurotrophic factors